2024
DOI: 10.1021/acs.jmedchem.3c02332
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Rule of Five and PROTACs in Modern Drug Discovery: Polarity Reducers, Chameleonicity, and the Evolving Physicochemical Landscape

Edward Price,
Manuel Weinheimer,
Alexey Rivkin
et al.

Abstract: Developing orally bioavailable drugs demands an understanding of absorption in early drug development. Traditional methods and physicochemical properties optimize absorption for rule of five (Ro5) compounds; beyond rule of five (bRo5) drugs necessitate advanced tools like the experimental measure of exposed polarity (EPSA) and the AbbVie multiparametric score (AB-MPS). Analyzing AB-MPS and EPSA against ∼1000 compounds with human absorption data and ∼10,000 AbbVie tool compounds (∼1000 proteolysis targeting chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Further evaluation of the internal global data set suggested that despite a slightly better performance of EPSA compared to TPSA for rank-ordering permeability, the correlation of EPSA with Caco-2 permeability for all compounds remains weak to moderate ( R 2 = 0.265, Figure A). This is not surprising as permeability is multidimensional and not solely driven by polarity. ,, A closer look at a PROTAC subset, characterized by compounds that on average are large (MW = 800), polar (TPSA = 200A), lipophilic ( c Log P = 6), and flexible (nRot = 12), shed light on the effectiveness of EPSA in rank-ordering continuously on permeability within a chemical space substantially outside the traditional “drug-like” space. In this context, EPSA provided improved permeability rank-order over TPSA and PAMPA (Figure B) owing to its unique ability to recognize the three-dimensional impact on polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Further evaluation of the internal global data set suggested that despite a slightly better performance of EPSA compared to TPSA for rank-ordering permeability, the correlation of EPSA with Caco-2 permeability for all compounds remains weak to moderate ( R 2 = 0.265, Figure A). This is not surprising as permeability is multidimensional and not solely driven by polarity. ,, A closer look at a PROTAC subset, characterized by compounds that on average are large (MW = 800), polar (TPSA = 200A), lipophilic ( c Log P = 6), and flexible (nRot = 12), shed light on the effectiveness of EPSA in rank-ordering continuously on permeability within a chemical space substantially outside the traditional “drug-like” space. In this context, EPSA provided improved permeability rank-order over TPSA and PAMPA (Figure B) owing to its unique ability to recognize the three-dimensional impact on polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Besides this approach, several powerful tools based on physicochemical compound parameters have been established [4][5][6]8]. However, our goal was to develop a cell-based high-throughput method which provides the determination of active cellular permeability and efflux for compounds in the bRo5 chemical space, with a focus on the possibility to predict the properties or rank-order compounds according to their expected intestinal absorption based on this cellular assay.…”
Section: Discussionmentioning
confidence: 99%
“…Besides a lack in predictability, traditional cellular permeability assays are often not able to generate a permeability value, because of low detection sensitivity due to the very low permeability, as well as nonspecific binding, of the compound to the incubation setup. Area (EPSA) [6], Chamelogk [7], and the EPSA-to-TPSA Ratio (ETR) [8], provide highthroughput support for bRo5 projects, especially at early stages [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing these bRo5 drugs requires a nuanced approach. The AbbVie multiparametric score (AB-MPS) goes beyond traditional metrics by incorporating factors like membrane permeability (LogD), aromatic rings, and rotatable bonds. , The “bRo5 and PROTACs in modern drug discovery” explores deeper into the concept of optimizing physicochemical properties for PROTACs. Recently, it proposed the use of the experimental polarity surface area (EPSA) alongside topological polar surface area (TPSA) to create a more informative metric: the EPSA-to-TPSA ratio (ETR) .…”
Section: Key Challenges and Opportunities For Protacmentioning
confidence: 99%